2000
DOI: 10.1021/jp994271b
|View full text |Cite
|
Sign up to set email alerts
|

Bistable Charge-Transfer Complex Formation of Redox-Active Organic Molecules Based on Intermolecular HOMO−LUMO Interaction Controlled by the Redox Reactions

Abstract: Bistable complex formation systems consisting of biphenylene (BP) and redox-active organic molecules such as chloranil (CL) and TCNE have been experimentally and theoretically investigated, based on an intermolecular interaction which characteristically occurs in the electrogenerated dianions forming a π-π type chargetransfer (CT) complex. Initially, we examined the CT complex formation of CL 2and TCNE 2with hydrocarbons (BP, hexamethylbenzene (HMB), and anthracene (AN)). Spectroelectrochemistry evidently gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…These studies clearly indicated that hydrogen bonding on its own can significantly alter the electrochemistry of quinoid compounds even though actual PT does not occur. Recently this was confirmed for several quinoid and phenolic systems that display inter-and intra-molecular hydrogen bonding [15,[17][18][19]24,[37][38][39][40][41][42]. Unlike the techniques used in such studies, 1 H NMR can provide direct evidence of hydrogen bonding, because molecular association in solution decreases the diffusion coefficient (D) of the species involved and the spatial location of hydrogen bonding within the molecules can be traced from the chemical shift in titration experiments [43].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These studies clearly indicated that hydrogen bonding on its own can significantly alter the electrochemistry of quinoid compounds even though actual PT does not occur. Recently this was confirmed for several quinoid and phenolic systems that display inter-and intra-molecular hydrogen bonding [15,[17][18][19]24,[37][38][39][40][41][42]. Unlike the techniques used in such studies, 1 H NMR can provide direct evidence of hydrogen bonding, because molecular association in solution decreases the diffusion coefficient (D) of the species involved and the spatial location of hydrogen bonding within the molecules can be traced from the chemical shift in titration experiments [43].…”
Section: Introductionmentioning
confidence: 94%
“…In the past, hydrogen bonding for quinoid systems has been inferred indirectly from UV-vis and computational studies. In addition, it has been inferred from standard mathematical treatments based on the redox shift of the voltammetric peaks caused by the association with the hydroxyllic reagents [1,[15][16][17][18][19][20][21][22][23][37][38][39]. These studies clearly indicated that hydrogen bonding on its own can significantly alter the electrochemistry of quinoid compounds even though actual PT does not occur.…”
Section: Introductionmentioning
confidence: 99%
“…The number of DH molecules involved in association by hydrogen bonding, as well as the respective association constants determined in this work, could also be analyzed with theoretical calculations [51,52] or through experimental data obtained using techniques other than those electrochemical procedures described herein [52 ± 54], however, such evaluations are beyond the scope of this work.…”
Section: Analysis Of Hydrogen Bonding Association With Different Alcomentioning
confidence: 99%
“…[17][18][19][20] The charge transfer properties of biphenylene have also found interest, and the structure of its radical cation, as well as inter-and intramolecular electron transfer in biphenylene-containing compounds have been studied. [21][22][23] As to the photophysical behaviour of the two [3]phenylenes, Niemeyer has revealed striking differences (in cyclohexane at room temperature): Whereas linear [3]phenylene (2a) was found to be non-fluorescent (Φ F < 10 -5 ), angular [3] 28 X-ray structure analysis data show also a strong alternance of the C-Cbond length in the central rings of the zig-zag [N]phenylenes. 5,29 In the present work, photophysical investigations of the linear and angular [3]phenylenes (2a), (3a), the zig-zag [4]-and [5]phenylenes (3b), (3c), and the triangular [4]phenylene (4) were performed (Fig.…”
Section: Introductionmentioning
confidence: 99%